UPANISAD PERSPEKTIF PENDIDIKAN MODERN - Ida bagus Putu eka Suadnyana; Krisna Sukma Yogiswari (Jurnal PASUPATI, 2019)
Book of the Upanishads is a book that can guide students to improve Sradha and Bhakti presented to Ida Sang Hyang Wasa Widhi. Upanishad is taken from the word "Upa" (near), "Ni" (Under), "Sad" (sit), so Upanishads means sitting under nearby. A group of students sitting near the teacher to learn the teachings of the Upanishads, reviewing the most essential issues and convey to students near them. This Upanishad it is a philosophical review of the Vedas, because every part of the review by the Upanishads Vedas, Upanishads thus derived contents and refer to the Vedas. education antiquity held in pesraman-pesraman or solitary place away from the crowds unlike now where the different methods and systems already using the system class. Along with the development of science and technology education pattern began to develop it, but it would be nice if such technological progress offset by an increase in human resources to the development of technology is not abused and still refers to the teachings of the religion, so it is important for the teacher to inculcate patterns of previous education contained in the Upanishads directed to students so that lessons and more easily understood by students. It is also important for a teacher to instill confidence in the Lord to the students, because the trust and of understanding the existence of Ida Sang Hyang Widi Wasa will give rise to positive thinking finally able to be applied by the students into a concrete action in accordance with the rules of religion.